The Relocation Planning of Logistics Port: Labuan Bajo Case Study - Rahmah, Fatchiyatur; Hasab, Iqbal Nur; Pratiwi , Wuryaningrum (Jurnal Transportasi: Sistem, Material, dan Infrastruktur, 2023)
The relocation of the Labuan Bajo Logistics Port to a multipurpose terminal at the new location of Wae Kelambu Village, West Manggarai (KM Number 30 of 2020) is impacted by the development of transportation facilities and infrastructure of the Ministry of Transportation. In addition, the BOR has reached 72%, and the waiting time is 4 days. Thus, a plan which can support the relocation of the new terminal by taking into account the hinterland potential is needed. The growing potentials are agricultural, plantation, fishery, manufacturing, and tourism sectors. The method used in this study was linear regression of load current with GRDP of West Manggarai. In the last year of the 20th, the projected payload reached 1,644,285 tons which assumes to be 68% container load and 32% general cargo load. There were 400 ship-calls from container ships and 742 ship-calls of general cargo ships. The land and water port facilities obtained the projected cargo and ship visit results. The water facilities consist of a shipping lane width of 210 m with a minimum depth of -9 m. The maximum area of the mooring pond was 11.5 ha, and the rotating pool was 3.6 ha. The onshore facilities consist of a 138 x 15 m dock and a 1,000 x 15 m trestle; a warehouse area of 670 m²; stacking area of 6,840 m². The investment cost for development was IDR 300 billion. In the 7th year, 2027, a 3,228 m² warehouse will be developed; in the 9th year, 2029, the procurement of loading and unloading equipment for Harbor Mobile Crane 2 units and a 19,737 m² stacking yard will be carried out as well. The impact of the relocation was to reduce ship operating costs by 37% -39% and 64% in docking costs. Providing income in port service from ships with a capacity of 736 TEUS of IDR 104 million per visit and increasing transportation fuel costs by 650%.